Ambulatory Extracorporeal Membrane Oxygenation with Subclavian Venoarterial Cannulation to Increase Mobility and Recovery in a Patient Awaiting Cardiac Transplantation. Issue 2 (1st April 2017) - Jacob, Samuel; Machannaford, Juan C.; Chamogeorgakis, Themistokles; Gonzalez-Stawinski, Gonzalo V.; Felius, Joost; Rafael, Aldo E.; Malyala, Rajasekhar S.; Lima, Brian
Abstract : Venoarterial extracorporeal membrane oxygenation (ECMO) can provide temporary cardiopulmonary support for patients in hemodynamic extremis or refractory heart failure until more durable therapies—such as cardiac transplantation or a left ventricular assist device—can be safely implemented. Conventional ECMO cannulation strategies commonly employ the femoral artery and vein, constraining the patients to the supine position for the duration of ECMO support. We have recently adopted a modified cannulation approach to promote patient mobility, rehabilitation, and faster recovery and to mitigate complications associated with femoral arterial cannulation, such as limb ischemia and compartment syndrome. This technique involves cannulation of the subclavian artery and vein. The current case report details our recent experience with this approach in a critically ill patient awaiting cardiac transplantation.